Development Of A Web-Based Information System For Proposing Academic Functional Positions For Lecturer At Stekoms Semarang - Ester Yuli Suprapti; Dani Sasmoko; Neilin Nikhlis (Lembaga Pengembangan Kinerja Dosen, 2023)
Semarang College of Electronics and Computers (STEKOM) which is based on Jl. Majapahit 605, has several campuses in Semarang and outside Semarang. With such campus location conditions, it makes it difficult for lecturers and related parties to process applications for Academic Functional Positions (JAFA). Lecturers have to repeatedly go to the central campus to process JAFA proposals and lecturers cannot know directly the extent of the credit figures that have been generated. Other related parties such as the personnel department, the Credit Score Assessment Team (TPAK) and STEKOM leadership find it difficult to monitor lecturers' activities in carrying out their tridharma duties. The Web-Based Information System for Proposing Academic Functional Positions for Lecturers which was developed using the Research and Development (R&D) method produces an application that will solve the problems surrounding JAFA proposals at STEKOM and can answer STEKOM's need for a JAFA lecturer proposal information system without being limited by place and time. . In creating this system, the author used Macromedia Dreamweaver MX 2004 software as the design medium and PHP as the programming language used, as well as the MySql database as the storage medium.